The Unified-Operation-Oriented Big Data Strategy for Telecom Operators - Jing Han; Zhijiang Zhang; Jianquan Wang; Yasong Wang (Dianxin kexue)
Firstly, the current situation on big data practice of telecom operators was introduced. Then challenges faced by local telecom operators when developing big data were summarized. Furthermore, the unified operation oriented big data strategy for telecom operators was proposed. Finally, inventory of big data assets and the architecture of big data service platform were described in detail.